2001
DOI: 10.1523/jneurosci.21-05-01444.2001
|View full text |Cite
|
Sign up to set email alerts
|

α-1-Antichymotrypsin Promotes β-Sheet Amyloid Plaque Deposition in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: ␣ 1 -Antichymotrypsin (ACT), an acute-phase inflammatory protein, is an integral component of the amyloid deposits in Alzheimer's disease (AD) and has been shown to catalyze amyloid ␤-peptide polymerization in vitro. We have investigated the impact of ACT on amyloid deposition in vivo by generating transgenic GFAP-ACT-expressing mice and crossing them with the PDGF-hAPP/V717F mice, which deposit amyloid in an agedependent manner. The number of amyloid deposits measured by Congo Red birefringence was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 48 publications
3
104
1
1
Order By: Relevance
“…Overexpression of human ACT accelerates amyloid pathology in human APP Tg mice (Mucke et al, 2000;Nilsson et al, 2001). Although ACT functions remain unclear and some reports about biochemical interactions with Ab are controversial, most evidence argues that ACT can play a causal role in amyloid aggregation and plaque formation, which is post-Abproduction (Ma et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of human ACT accelerates amyloid pathology in human APP Tg mice (Mucke et al, 2000;Nilsson et al, 2001). Although ACT functions remain unclear and some reports about biochemical interactions with Ab are controversial, most evidence argues that ACT can play a causal role in amyloid aggregation and plaque formation, which is post-Abproduction (Ma et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…ACT is an acute phase protein induced by inflammation (Akiyama et al, 2000) as well as a pro-amyloidogenic molecule (Mucke et al, 2000;Nilsson et al, 2001). In our experiments, the analysis of ACT was performed in human and mouse material rather than in the rat infusion model, because a rat homolog of ACT has not been adequately identified.…”
Section: Bace Mrna Was Not Suppressed By Ibuprofenmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusively, neuronal expression of the APP transgenes with neuron-specific promoters resulted in plaques with a regional distribution and characteristic relationships with glia that strongly resemble AD [24,28,57] providing compelling evidence for a neuronal source of the A␤ in deposits. Manipulation of these models has also provided solid evidence that two of the astrocyte protein products, ApoE [4] and ␣1-ACT [45,49], play an important role in amyloid plaque deposition. Therefore, one must cede the point that astrocytes "contribute" to plaque formation or progression although there is also strong evidence for an astrocytic role in amyloid clearance [46,71].…”
Section: Glial Activation and Amyloid Plaque Formation In App Transgementioning
confidence: 99%
“…Although ACT is predominantly produced in the liver, it is also synthesized in the brain, mainly by astrocytes. 2 Studies in transgenic mouse models of AD revealed that ACT accelerates and enhances amyloid plaque formation, 3,4 which suggests a role for ACT in AD pathophysiology. Elevated levels of ACT are found in the brain, serum and cerebrospinal fluid (CSF) 5 -9 of AD patients and high ACT in plasma is associated with cognitive decline in elderly subjects.…”
Section: Introductionmentioning
confidence: 99%